Highly Efficient Cardiac Differentiation and Maintenance by Thrombin-Coagulated Fibrin Hydrogels Enriched with Decellularized Porcine Heart Extracellular Matrix - Navaee, Fatemeh; Renaud, Philippe; Kleger, Alexander; Braschler, Thomas (International journal of molecular sciences, 2023)
Biochemical and biophysical properties instruct cardiac tissue morphogenesis. Here, we are reporting on a blend of cardiac decellularized extracellular matrix (dECM) from porcine ventricular tissue and fibrinogen that is suitable for investigations employing an in vitro 3D cardiac cell culture model. Rapid and specific coagulation with thrombin facilitates the gentle inclusion of cells while avoiding sedimentation during formation of the dECM-fibrin composite. Our investigations revealed enhanced cardiogenic differentiation in the H9c2 myoblast cells when using the system in a co-culture with Nor-10 fibroblasts. Further enhancement of differentiation efficiency was achieved by 3D embedding of rat neonatal cardiomyocytes in the 3D system. Calcium imaging and analysis of beating motion both indicate that the dECM-fibrin composite significantly enhances recovery, frequency, synchrony, and the maintenance of spontaneous beating, as compared to various controls including Matrigel, pure fibrin and collagen I as well as a fibrin-collagen I blend.